Cardiac Mortality in Kidney Transplant Patients: A Population-based Cohort Study 1988–2013 in Australia and New Zealand. Issue 2 (10th March 2020) - Wyld, Melanie L.R.; De La Mata, Nicole L.; Masson, Philip; O'Lone, Emma; Kelly, Patrick J.; Webster, Angela C.
Abstract : Background: Transplant recipients experience excess cardiac mortality. We compared circulatory death rates in Australian and New Zealand kidney transplant recipients to the general population and identified risk factors for circulatory death in kidney transplant recipients. Methods: The primary cause of death for kidney transplant recipients aged ≥18 was established through ICD-10-AM codes using data linkage between the Australia and New Zealand dialysis and transplant registry and national death registers. We estimated standardized mortality ratios (SMRs) and developed a Fine–Gray competing risks model to determine risk factors for cardiac mortality. Results: Of 5089 deaths in 16 329 kidney transplant recipients (158 325 person-years), 918 (18%) were cardiac. An increased risk of circulatory death was associated with older age ( P < 0.001), male sex ( P < 0.001), longer dialysis duration ( P = 0.004), earlier era of transplantation ( P < 0.001), ever graft failure ( P < 0.001), known coronary artery disease ( P = 0.002), and kidney failure from diabetes or hypertension ( P < 0.001). The cardiac SMR was 5.4 [95% confidence interval (CI): 5.0-5.8], falling from 8.0 (95% CI: 4.9-13.1) in 1988 to 5.3 (95% CI: 4.0-7.0) in 2013 ( P < 0.001). Females, particularly young ones, had significantly higher relative cardiac mortality than men. In recipients aged 40 years, the cardiac SMR was 26.5 (95% CI: 15.0-46.6) in females and 7.5 (95% CI: 5.0-11.1) for males. Conclusions: Cardiac risks remain elevated in kidney transplant recipients and may be under-recognized, and prevention and treatment interventions less accessed, less effective or even harmful in female recipients.